Resilience on Climate Change Through the Literature - Motevalli, Saeid; Bin Abu Talib, Mansor; John Henshaw, Christopher; Nee Nee, Chan; Roda, Jean-Marc; Shaker Al-Shaibani, Ghayth Kamel (International Journal of Education and Cognitive Sciences, 2022)
It is vital to understand resilience as it applies to the field of climate change and disaster. The concept of resilience has drawn the interest of climate scientists and psychologists who want to better understand how we can improve individual's and society’s resilience in the face of a quickly worsening climate as a result of man-made climate change. Resilience is defined as a process, ability, or outcome of successful adaptation to the environment, despite dangerous or adverse conditions. The objective of this study is to run review research through contemporary studies to summarise the cumulative documents in the area of resilience and climate change to investigate the contributing factors to climate change resilience. A search was carried out on the Web of Science, Google Scholar, and PubMed. A set of keywords was used, followed by filtering main keywords, resulting in a review of 70 articles. The results demonstrated that resilience was the main target of various researchers on climate change globally. Moreover, results indicate various waves of resilience and components of resilience including exposure, susceptibility, and capacity to cope with environmental issues. Besides that, this research revealed coping strategies on climate change and factors that have been correlated with climate change resilience (e.g., psychological, social, and family and community factors). In conclusion, resilience has been identified as a core concept in both the mitigation of climate change and climate change disasters, as well as the capacity to cope with these when they occur. Future research should focus on identifying core